2019
DOI: 10.3390/molecules24040732
|View full text |Cite
|
Sign up to set email alerts
|

Review of Ethnomedicinal, Phytochemical and Pharmacological Properties of Lannea schweinfurthii (Engl.) Engl.

Abstract: Lannea schweinfurthii is a valuable medicinal plant species among different ethnic groups in tropical Africa. The aim of the current study was to review existing literature on the ethnomedicinal uses, phytochemistry and pharmacological properties of L. schweinfurthii in an effort to evaluate the therapeutic potential of the species. The relevant information on the ethnomedicinal uses, phytochemistry and pharmacological properties of L. schweinfurthii was generated from several sources including books, book cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…More illustratively, it could be argued that potential side effects of Bolebatša could cause the forgetfulness of other essential memories of the service users. Although the herb appears to be meaningful in the traditional healing enterprise, from the scientific paradigm it remains elusive regarding its efficacy, brain interaction sites and mechanism of action (Maroyi, 2019; Magwede et al , 2019). This therefore warrants further investigations on the herb or perhaps the traditional healing paradigm undergird by the philosophy of holism (Bouso and Sanchez-Aviles, 2020), could better account for the identified limitations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…More illustratively, it could be argued that potential side effects of Bolebatša could cause the forgetfulness of other essential memories of the service users. Although the herb appears to be meaningful in the traditional healing enterprise, from the scientific paradigm it remains elusive regarding its efficacy, brain interaction sites and mechanism of action (Maroyi, 2019; Magwede et al , 2019). This therefore warrants further investigations on the herb or perhaps the traditional healing paradigm undergird by the philosophy of holism (Bouso and Sanchez-Aviles, 2020), could better account for the identified limitations.…”
Section: Resultsmentioning
confidence: 99%
“…One medicinal plant noted for numerous health-care benefits in most regions of Africa is derived from Lannea schweinfurthii var. stuhlmannii (Maroyi, 2019). Lannea schweinfurthii is a small to medium-sized deciduous tree with hairy patches growing on its roots and belongs to the wild currant or Anacardiaceae family (Kotina et al , 2018; Magwede et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Methanol extract of Lannea schweinfurthii Engl., Anacardiaceae, stem bark shows strong antiviral activities against herpes simplex virus type 1, vesicular stomatitis virus T2, Coxsackie B2, and Semliki Forest A7 in a research carried out by Maregesi et al (2008). In vitro study conducted by Maregesi et al (2010), using the microdilution assay, also demonstrated the anti-HIV activities of aqueous and methanol extracts of L. schweinfurthii stem bark against human immunodeficiency virus type 1 (HIV-1, IIIB strain) and type 2 (HIV-2, ROD strain) and established the superior efficacy of the 80% methanol extract (Maroyi 2019).…”
Section: Lannea Schweinfurthii Englmentioning
confidence: 88%